2019
DOI: 10.5194/acp-19-4485-2019
|View full text |Cite
|
Sign up to set email alerts
|

Can VHF radars at polar latitudes measure mean vertical winds in the presence of PMSE?

Abstract: Mean vertical velocity measurements obtained from radars at polar latitudes using polar mesosphere summer echoes (PMSEs) as an inert tracer have been considered to be non-representative of the mean vertical winds over the last couple of decades. We used PMSEs observed with the Middle Atmosphere Alomar Radar System (MAARSY) over Andøya, Norway (69.30 • N, 16.04 • E), during summers of 2016 and 2017 to derive mean vertical winds in the upper mesosphere. The 3-D vector wind components (zonal, meridional and verti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…At midlatitudes and high latitudes, semidiurnal tides are the dominating tidal wave during the course of the year (Hagan and Forbes, 2002Forbes, , 2003. Figure 5 shows the vectoraveraged semidiurnal tidal amplitudes measured by all six meteor radars using again a 30 d median shifted by 1 d in analogy to the mean winds and diurnal tides.…”
Section: Semidiurnal Tidal Amplitudes and Phases Measured During 2019mentioning
confidence: 99%
“…At midlatitudes and high latitudes, semidiurnal tides are the dominating tidal wave during the course of the year (Hagan and Forbes, 2002Forbes, , 2003. Figure 5 shows the vectoraveraged semidiurnal tidal amplitudes measured by all six meteor radars using again a 30 d median shifted by 1 d in analogy to the mean winds and diurnal tides.…”
Section: Semidiurnal Tidal Amplitudes and Phases Measured During 2019mentioning
confidence: 99%
“…According to these research results, it can be seen that the tidal amplitude in the vertical wind in the 65–85 km heights is smaller than that in higher altitudes (above 90 km) and may not exceed the mean vertical wind. Furthermore, Gudadze et al (2019) showed that there was no significant diurnal variation in the vertical wind observed with the PMSEs which exist all day in summer at high latitude. Eswaraiah et al (2011) stated that the effect of the diurnal and semidiurnal tidal amplitude is smaller at the mesospheric altitudes compared with those at higher altitudes (~85 km).…”
Section: Resultsmentioning
confidence: 96%
“…These correlations arise from the turbulence and gravity wave motion and can lead to the downward biases in the measured mean vertical velocity. Gudadze et al (2019) further studied these correlations with the long-term observations of the PMSEs by the MAARSY radar. However, they have found the contrary results, that is the negative correlation between the downward vertical wind and the velocity uncertainties.…”
Section: 1029/2020jd032776mentioning
confidence: 99%
See 2 more Smart Citations